Suburban urbanities : suburbs and the life of the High street (2015)
In recent years there has been much debate within urban studies as to which came first in the evolution of human settlements, the countryside or the city. There was always a third context to this discussion, however, and that was the suburb. Life beyond the city walls was a distinctive feature of ancient urban civilisations from Persia to Minoan Crete, and today in the Anglophone world the suburban population is a majority. How surprising, then, that few scholars have attempted to understand the nature and agency of suburban living as a dominant characteristic of human settlements. This was symptomatic of a wider academic indifference and even hostility towards ‘the suburban’ which has only (ridiculously) recently been challenged by a new generation of scholars who take suburbs seriously. Suburban Urbanities is a hugely important contribution to understanding our suburban world. Drawing upon scholarship within the now rapidly expanding field of suburban studies, synthesising historical geography with space syntax theories and methods, and the sociology of everyday life, it sheds new light on the historic and spatial evolution of the city. It shows that suburbia is not a synchronic caricature of a life-less-lived, but a dynamic context of metropolitan agency and creativity. As an historic process, suburbanisation is not something that evolved beyond the city to suck the life out of it, but was intertwined with trajectories of growth, with the socioeconomic patterning and structuring of cities large and small. It is impossible to grasp the meaning of class relations, of gendered lifestyles, of ethnic segregation and integration, of urban economies and patterns of mobility and communications, without placing suburbia at the forefront of the analysis. The universality of the themes of Suburban Urbanities is obvious: the dynamics of growth are significant historically because suburbs are starting points in change over time, not the end of the line. Old suburbs were once new, and today’s new suburbs, springing up rapidly across the world, will one day be old. As dynamic environments they continue to act as vectors of social, economic and political development, locally, nationally and globally